Determination of rare earth elements in saline matrices using dispersed particle extraction and inductively coupled plasma mass spectrometry. (4th May 2014) - Janski, Rafael; Neouze, Marie‐Alexandra; Limbeck, Andreas
<x xml:space="preserve">Abstract</x> RATIONALE Rare earth elements play an important role in identifying and indexing the origin of historical and geological samples. In this work, a new approach for the characterization of rare earth elements (REEs) in aqueous sample solutions with high salinity is presented. METHODS Prior to analysis by inductively coupled plasma mass spectrometry (ICP‐MS) the target analytes were separated from interfering matrix constituents by the use of surface‐functionalized nanoparticles. Compared with common matrix separation techniques, such as solid‐phase extraction (SPE), the strength of the method lies in the combination of an advanced extraction procedure with internal standard correction. Thus, known limitations of SPE such as column clogging or incomplete analyte elution could be completely circumvented. Furthermore, time‐consuming approaches for signal quantification such as matrix‐matched calibration could be avoided since the applied internal standard allows the correction of matrix‐induced deviations in sample extraction and ICP‐MS analysis. RESULTS With the developed procedure detection limits <1 ng L−1 could be achieved for all the investigated elements, with satisfactory relative standard deviations (RSDs) of 3–26% for unspiked samples and <1–2% for spiked samples. Results derived from recovery experiments with spiked oil accumulation water samples confirmed the applicability of the proposed procedure for the determination of REEs in highly saline sample solutions. The procedure was successfully applied to the study of oil accumulation water samples from different oil fields in Lower Austria. CONCLUSIONS A sample pretreatment procedure with subsequent ICP‐MS analysis for the accurate determination of REEs in aqueous sample solutions with high salinity has been developed. Copyright © 2014 John Wiley & Sons, Ltd.